Pharmacoeconomic study of nutrition support in the conditions of current health care system in Russia - I. A. Metelkin; R. I. Yagudina (Фармакоэкономика, 2015)
Objectives: Definition of the most rational method of nutrition support (comparison of three methods – enteral, parenteral and mixed nutrition) applied during therapy among different patients depending on their health condition on means of carrying out the pharmacoeconomic study. Methods: Pharmacoeconomic analysis: «budget impact analysis» and «lost opportunities analysis» was provided. Only direct costs were taken into account: expenses for drug therapy, hospitalization (intensive care unit and medical division) and late complications (pneumonia, sepsis, catheter and wound infection) treatment. Effectiveness data was taken from Russian clinical trial: Popov T.S., Shestopalov A.E., Tsvetkov D.S., Nechaev D.S., Kuz’min M.A. Nutrition Day in intensive care units of the Russian Federation. National association of parenteral and enteral nutrition – Moscow (Russia), 2011. Four types of treatment were compared: intensive treatment (IT) + enteral nutrition (EN); IT + parenteral nutrition (PN); IT + mixed nutrition (MN) and IT without nutrition support (NS). Results: When carrying out comparative pharmacoeconomic study all calculations were made for 3 groups of patients depending on their health condition: lightly-severe, moderately severe and severe. According to the results of calculations transfer of patients from IT without NS to IT carrying out NS leads to reduction of total expenses, therefore economy of money for the state. Independent from patient health condition – the greatest economy of money arises when EN is used during IT. Further on degree of expressiveness of positive economic effect there is PN and the least NS economic type is MN. Results of «lost opportunities analysis» showed that transfer of 1 000 patients from IT without NS, to therapy taking into account EN, provides an opportunity to over treat 496; 660 and 473 patients of the following health conditions: lightly-severe, moderately severe and severe. The results gained at all steps of research maintained the multiple-factor sensitivity analysis (+/-20% of the cost of secondary complications of the main disease therapy standards, the hospitalization cost and NS cost) that proves stability of the received results. Conclusions: Method of NS - EN independent from patients health condition is the most economic and practic for application during IT. That is why, it can be recommended as a dominant alternative. Thus IT without NS, is associated with considerable financial expenses, therefore, economically not viable.